Enhancing Customer Satisfaction in Internet Service: Unveiling the Key Factors - Pradeep Acharya; Omkar Poudel (Journal of Business and Social Sciences, 2022)
With the development of technology, there has been also the simultaneous development and advancement in the internet service and also the number of people using the internet service has been increasing every day. Thus, the number of internet service providers has also increased with time and it’s hard to decide to choose from the lot of options available. Thus, the service providers should also work to increase the satisfaction of the customers. Keeping this in mind the purpose of the study is to examine the impact of network quality, price, trust and perceived value under study on customer’s satisfaction towards internet service providers. Data from 244 valid samples were recorded and analyzed using partial least square structural equation modeling (PLS-SEM) to determine the result of the study. The analysis of the study indicated that Network quality, Price and Perceived value have a significant positive impact on customer satisfaction and Trust of the customers towards internet service providers has no significant impact on customer satisfaction.